American versus domestic digital companies in the Chinese market - Lukács, Eszter; Völgyi, Katalin; Kovács, Norbert; Tóth, Árpád (Decision Making: Applications in Management and Engineering, 2022)
The digital economy has become an increasingly important part of the world economy. It is vastly concentrated in two economies, namely, the United States and China. The main aim of our study is to investigate Chinese digital companies and government policy enabling the rapid development of the country’s digital economy and the largest American digital companies’ performance in the Chinese market. Our findings show that the largest American digital companies, which are globally active players, usually have a very limited market share in different segments of the Chinese digital economy or have been forced to leave the Chinese market after a short period of operation. In the future, Chinese government policy will continue to ensure the priority role of domestic digital companies in the upgrading and structural transformation of the Chinese economy driven by services, high-tech sectors, and consumption while limiting the role of American digital companies.